SOSIALISASI DAN PELATIHAN HIDROPONIK SISTEM SEDERHANA PADA MAHASISWA UKIP SORONG (PENYEMAIAN BENIH) - Leiwakabessy, Ivonne (SOLIDEO Jurnal Pengabdian Masyarakat, 2024)
Yard utilization by applying simple hydroponic planting, training in pakcoy plant cultivation on a household scale is needed. The method used in this community service is socialization and training (practice) which is carried out in several stages, namely: 1) Lecture/delivery of material, this activity is the stage of introduction and training to community service participants/partners regarding pakcoy plant cultivation using a hydroponic system; 2) Question and answer, this activity was carried out after the delivery of simple and useful hydroponic introduction material to see the interests and knowledge of partners related to the material presented; 3) Practice of making planting media by planting pakcoy seed seedlingsAs a result of this service activity, students can find out the stages in vegetable cultivation with a hydroponic system, so that students are trained to be more dexterous by utilizing used items that can be reprocessed, such as used plastic cups or used plastic bottles that can be processed as planting media. With a hydroponic system, the vegetables produced have many advantages for the body, besides that the vegetables that are digested are free from residues and pests and diseases. Other profits can be consumed by themselves as personal needs and as commercial needs to be sold